Implementasi Server Virtualisasi Menggunakan Proxmox untuk Manajemen Infrastruktur Jaringan dan Layanan Internet pada Institusi Pendidikan - Rido Rido; Mohammad Rezza Pahlevi; Imam Maliki; Muhammad Iqbal (Universitas Indonesia Membangun (Inaba), 2026)
Modern educational institutions face challenges in managing complex information technologyinfrastructure with limited resources. This research examines the implementation of virtualizationtechnology using Proxmox Virtual Environment to optimize server management, computer networks, and internet services in higher education environments. The research method uses a case studyapproach with data collection through direct observation, interviews with 12 informants, systemdocumentation, and performance monitoring over 6 months. The results show that ProxmoxVEimplementation can increase hardware resource ef iciency by up to 70 percent with CPUutilizationincreasing from 22 percent to 50-55 percent. Physical server consolidation from 12 units to3host servers successfully reduced operational costs by 45 percent or 35,650 per year. Service availabilityincreased significantly from 96.8 percent to 99.5 percent with Mean Time To Recovery reducedfrom4 hours to 45 minutes. Cost-benefit analysis shows Return on Investment achieved in 2.9 years withprojected Total Cost of Ownership savings of 73,250 over a 5-year period. This research providespractical contributions in the form of virtualization architecture blueprints and implementationguidelines that can be adopted by other educational institutions with similar characteristics.